ORGANIZATIONAL AND PERSONALITY EFFECTS ON MANAGERSâ JOB STRESS: Is It Different for Malaysian Men and Women? - Nasurdin, Aizzat Mohd.; Ramayah, T.; Kumaresan, S. (Gadjah Mada International Journal of Business, 2004)
The purpose of this paper is to determine the influence of organizational variables (conflict, blocked career, alienation, work overload, and unfavorable work environment) and personality variables (neuroticism, extraversion, openness, agreeableness, and conscientiousness) on job stress among managers working in the electronics sector in 4Malaysia and whether this relationship varies according to their gender. Analyses of 285 responses using hierarchical regression revealed that four of five organizational variables (blocked career, alienation, work overload, and conflict) had significant positive effects on job stress. In terms of the personality traits, neuroticism and conscientiousness were found to be significantly and positively related to stress. Extraversion and agreeableness, on the other hand, had significant negative effects on job stress. Gender was found to moderate the effects of all the independent variables on job stress at the 0.01 level. Implications for managerial practice and future research are discussed.